1988
DOI: 10.1104/pp.88.3.833
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ethylene Biosynthesis by Salicylic Acid

Abstract: ABSTRACISalicylic acid inhibited ethylene formation from ACC in self-buffered (pH 3.8) pear (Pyrus communis) cell suspension cultures with a K1'PP of about 10 micromolar after 1 to 3 hours incubation. Inhibition appeared noncompetitive. Among 22 related phenolic compounds tested, only acetylsalicylic acid showed similar levels of inhibition. Inhibition by salicylic acid was inversely dependent on the pH of the culture medium and did not require a continuous external supply of salicylate. When compared to known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
109
0
5

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(120 citation statements)
references
References 21 publications
6
109
0
5
Order By: Relevance
“…Breaker stage maturity is the time when increase in the production of ethylene is usually observed [30,31]. The findings of Ding and Wang [29] confirmed that SA has the ability to reduce ethylene production [32] and delay ripening. A similar observation has been reported in kiwi dipped in ASA at 1000 µmol l -1 for 5 min [33,34], in strawberries, treated with SA at 1000-4000 µmol l -1 [35], in custard apples dipped in SA at 400, 800 and 1200 µmol l -1 for 15 min [25].…”
Section: Physiological Effects Respirationsupporting
confidence: 55%
“…Breaker stage maturity is the time when increase in the production of ethylene is usually observed [30,31]. The findings of Ding and Wang [29] confirmed that SA has the ability to reduce ethylene production [32] and delay ripening. A similar observation has been reported in kiwi dipped in ASA at 1000 µmol l -1 for 5 min [33,34], in strawberries, treated with SA at 1000-4000 µmol l -1 [35], in custard apples dipped in SA at 400, 800 and 1200 µmol l -1 for 15 min [25].…”
Section: Physiological Effects Respirationsupporting
confidence: 55%
“…This notion is further strengthened by the fact that SA down-regulated both the developmentally expressed and the induced transcripts. However, SA seems capable of affecting several putative gene-regulatory pathways (Dempsey and Klessig, 1995;Doares et al, 1995;Leslie and Romani, 1988;Pena-Cortes et al, 1993;Wildon et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, salicylic acid has been proposed as a new kind of plant hormone that led to the higher firmness of fruits and lower fruit chilling injury and decay incidences (Rao et al, 2011). Leslie and Romarini (1988) stated that salicylic acid as a simple phenolic compound maintains firmness by regulating the expression of genes involved in ACC synthase and ACC oxidase enzyme, and reducing ethylene production and cell wall degrading enzymes such as polygalacturonase, cellulase and pectinase (Shafiee et al, 2010). Zhang et al (2003) reported that salicylic acid affected cell walls and caused fruit to be stronger.…”
Section: Titratable Acidity (Ta)mentioning
confidence: 99%